BISNIS DAN TANGUNG JAWAB SOSIAL - -, Sarwono (Innofarm:Jurnal Inovasi Pertanian, 2010)
ABSTRACT The dynamic of the eviroment which are caused by the internal and ekternal causer have forced the businessmen not onlyÂ  to increase the profit and work systems but also to care for social problems. The more power the businessmen have the more significant effectÂ  of life the people have, whether as individual or as society. Even, it influences all lives in the word. This phenomenon brings the statement of Corporate Social Responsibility (CSR). CSR emphasizes that the responsibility of a company is not just for economic activities (creating profit for the continuity of the business), but also for the social responsibility including the environment. The social responsibility in the field of business, is not only oriented on social commitment which emphasizes on humanism approach, love, interest in religion, morality, and the like, but also duties that must be done by the businessmen to solve the social problems appeared in the society. In its development CSR has much been purposely done, it means that applying CSR is the investment of the development and the continuity of the business do the business is not considered as cost but as profit. Even, now days CSR has become the global trend. Key word: corporate social responsibility